2022
DOI: 10.3390/agronomy12071530
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Fertilizer and Microbial Agents Changed the Bacterial Community in the Consecutive Replant Soil of Lilies

Abstract: Crop replanting leads to soil degradation and soil productivity reduction, which is a challenge for sustainable agricultural development. We previously found that silicon fertilizers combined with additional microbial agents are an effective means to alleviate problems that occur in a variety of Chinese lily during replanting, but little is known about the changes in microbial structure during this process. In the present study, we applied four treatments: CK (control), SF (silicon fertilizer), MF (microbial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…These findings are consistent with a previous study that integrated biological control methods and effectively suppressed tobacco bacterial wilt by regulating the soil physicochemical properties, and promoting beneficial and antagonistic bacteria in the rhizosphere soil [52]. The longer arrows in the RDA ordinations (Figure 1) indicated that pH had a stronger effect on bacteria and fungi than the other physicochemical properties, which is consistent with the findings of Shi et al [53] and Yu et al [54]. A redundancy analysis was performed to examine the relationship between the soil edaphic properties and the diversity of microbial communities in the four groups of soil samples.…”
Section: Effects Of Bacillus Bf1 and Y37 On Soil Physicochemical Prop...supporting
confidence: 93%
“…These findings are consistent with a previous study that integrated biological control methods and effectively suppressed tobacco bacterial wilt by regulating the soil physicochemical properties, and promoting beneficial and antagonistic bacteria in the rhizosphere soil [52]. The longer arrows in the RDA ordinations (Figure 1) indicated that pH had a stronger effect on bacteria and fungi than the other physicochemical properties, which is consistent with the findings of Shi et al [53] and Yu et al [54]. A redundancy analysis was performed to examine the relationship between the soil edaphic properties and the diversity of microbial communities in the four groups of soil samples.…”
Section: Effects Of Bacillus Bf1 and Y37 On Soil Physicochemical Prop...supporting
confidence: 93%
“…Actinobacteria has important functions in improving soil conditions through debris decomposition, and in promoting microbial growth via secondary metabolites and enzyme production (Selim et al, 2021). While the Actinobacteria was less abundant with higher grazing intensity (Ling et al, 2022; Yu et al, 2022). These findings suggested that the extreme habitat induced by heavy grazing severely influenced the soil bacterial structure and the associated functions.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteroidota and Firmicutes which are intestinal microorganisms, were also abundant in grazing areas, possibly due to fecal excretion (Fan & Pedersen, 2021). However, Proteobacteria is known for the ability to decompose recalcitrant carbon, but was unexpectedly to decrease with increasing grazing intensity (He et al, 2022;Yu et al, 2022). Actinobacteria has important functions in improving soil conditions through debris decomposition, and in promoting microbial growth via secondary metabolites and enzyme production (Selim et al, 2021).…”
Section: The Effect Of Environmental Factors On Soil Bacterial Commun...mentioning
confidence: 99%
“…We observed that bacterial phyla, including Proteobacteria, Acidobacteria, Actinobacteria, and two fungal phyla Ascomycota and Basidiomycota are the most prevalent groups that were consistently enriched in that perspective order, irrespective of the cultivar type and treatment (Figure 1). A recent study on the bacterial communities has shown the dominant trends of these phyla, that were affected under longterm fertilization and both silicate and microbial agent applications (Li et al, 2021;Yu et al, 2022). Both Ascomycota and Basidiomycota, are the two most dominant fungal phyla that participate in degradation processes (decomposers) (Morrison et al, 2016;Egidi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%